2-D Crack propagation analysis using stable generalized finite element method with global-local enrichments. (September 2020) - Fonseca, Gabriela M.; Barros, Felício B.; de Oliveira, Thaianne S.; Monteiro, Humberto A.S.; Novelli, Larissa; Pitangueira, Roque L.S.
Abstract: In this paper, the technique of the Stable Generalized Finite Element Method (SGFEM) is applied to the numerically constructed functions of the Generalized Finite Element Method with Global-Local Enrichments (GFEM gl ). The application of the resulting approach, named SGFEM gl, is expanded here to 2-D quasi-static crack propagation problems. Crack growth is performed by a two-scale strategy, using local problems generated at each propagation step – whose solutions enrich a single global problem defined on a coarse mesh. Stress Intensity Factors (SIFs) computed along crack growth, strain energy measures, performance in blending elements and the condition number are used to study the accuracy and conditioning of SGFEM gl . The method is compared with the standard GFEM gl . Numerical experiments demonstrate remarkable accuracy of SGFEM gl in linear elastic fracture mechanics problems, considering crack opening modes I and II. Convergence rates analyses also show the superiority of the method, especially with the use of geometrical enrichments.